THE DEVELOPMENT OF THE SCIENCE OF FIQH IN MOVAROUNNAHR IN THE 13TH–14TH CENTURIES (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the process of the development of the science of fiqh(Islamic jurisprudence) in Movarounnahr (Transoxiana) in the 13th–14th centuries,its principal features, and its scholarly environment. It shows that, despite the politicalchanges in the region during this period, the juridical traditions continued consistently.The scholarly legacy of the jurists (faqihs) is illuminated, and the contribution of the localscholars (ulama) to the development of the science of fiqh in Movarounnahr is analyzed.
Keywords: scholar, fiqh, usul al-fiqh, furu al-fiqh, legacy, abridged (mukhtasar) work, fatawa, versification (nazm), translation, Mongols, families of jurists.